Assessing Β-carboline Analogues As Antibiotic Agent Using In Vitro Studies - Nur Anis Afiqah Jasmin; Nurasyikin Hamzah; Nurul Iman Aminudin; Shafida Abd Hamid; Noor Hidayah Pungot; Rahayu Ahmad (Asian Scholars Network, 2024)
Non-Index Publication